Lexical and sublexical orthographic knowledge: relationships in an orthography of intermediate depth - Querido, L.; Fernandes, S.; Verhaeghe. A.; Marques, C. (Reading and Writing, 2020)
It is widely accepted that orthographic knowledge comprises two components: wordspecific orthographic knowledge, also termed lexical orthographic knowledge, and general orthographic knowledge, or sublexical orthographic knowledge. Until now, the study of the relationship between these components throughout literacy development has been somehow neglected. In this study, we examined how they are related at an early stage of literacy development in European Portuguese, an orthography of intermediate depth. Children followed from Grade 2 to 3 performed two of the most common tasks of orthographic knowledge – the Orthographic Choice Task and the Orthographic Awareness Task. Crossed-lagged structural equation modeling showed significant mutual contributions between the two components of orthographic knowledge, providing thus preliminary evidence of bidirectional relations over time. Results are discussed in the context of theories of reading development taking into account the influence of orthography consistency.